PERANCANGAN STRATEGIS SISTEM INFORMASI Studi Kasus : Universitas Yudha Wastu - Harmon Lumbanraja (Jurakunman (Jurnal Akuntansi dan Manajemen), 2018)
Yudha Wisnu University is in an environment with information technology that continues to grow, develop and greatly affect human life, coupled with the aggressiveness of market participants (universities, educational institutions, course institutions and certification institutions) that are so high to take advantage of advances in technological developments and information systems in order to achieve opportunities in the smallest market share. The methodologies used in the organization's business strategy are: Business environment analysis, IS / IT environmental analysis, IS / IT planning, organization, human resources and investment for IS / IT planning, IS / IT management proposals from IS / IT evaluation at the University Yudha Wisnu as described in the previous section, can be concluded that the level of establishment of information technology at Yudha Wisnu University. Information technology management human resources already have knowledge of issues related to information technology governance activities, and have taken appropriate actions even more to solve problems related to information technology services, Activities to further improve technology governance information that is currently running cannot yet be implemented. To that end, several recommendations that can be submitted in order to increase the level of establishment of information technology at Yudha Wisnu University are: Establish a strategic policy for the use of information technology as the basis for the preparation of rules and guidelines for information technology governance at Yudha Wisnu University.